Sudden-onset transient bilateral myopia and angle closure induced by indapamide - Katarzyna Samelska; Ewa Strzemecka; Piotr Skopiński; Anna Zaleska-Żmijewska (Klinika Oczna)
We present a 34-year-old patient with sudden bilateral worsening of vision. The ophthalmic examination revealed myopia, anterior chamber shallowing and acute angle closure in both eyes. The patient had initiated systemic hypertension therapy with indapamide 14 days prior to the onset of symptoms. Intraocular pressure (IOP) was elevated in both eyes (28 mmHg in right eye, 32 mmHg in left eye). Images of the anterior segment of the eye were obtained with anterior segment optical coherence tomography (AS-OCT). The anterior chamber depth (ACD) and iridotrabecular contact were measured in both eyes. The symptoms resolved three days later. The ophthalmic examination showed normal IOP and AS-OCT image. Acute-onset bilateral myopia accompanied by acute angle closure may be a side-effect of the use of systemic drugs such as topiramate, sulphonamides and, in this case, indapamide. The treatment includes causative agent withdrawal and ocular anti-hypertensive topical therapy. The case report underlines the importance of knowledge of systemic drugs’ side-effects on the eye.